Perfusion strategy using axillary or femoral cannulation for minimally invasive cardiac surgery: experience in 270 patients with computed tomography-based criteria. (15th January 2021) - Nakamura, Yoshitsugu; Nishijima, Shuhei; Kuroda, Miho; Nakayama, Taisuke; Tsuruta, Ryo; Yoshiyama, Daiki; Yasumoto, Yuto; Ito, Yujiro
Abstract:  : OBJECTIVES: In patients with atherosclerotic disease, minimally invasive cardiac surgery using retrograde perfusion for cardiopulmonary bypass via femoral cannulation (FC) carries a higher risk of brain embolization compared with antegrade perfusion. However, guidelines for selecting antegrade versus retrograde perfusion do not exist. We developed a computed tomography (CT)-based perfusion strategy and assessed outcomes. METHODS: We studied 270 minimally invasive cardiac surgery patients, aged 68 ± 13, 124 female, body surface area 1.6 ± 0.2 m 2 . Antegrade perfusion using axillary cannulation (AC) was selected if any of the following preoperative enhanced CT scan criteria were satisfied anywhere in the aorta or iliac arteries: thrombosis thickness >3 mm, thrombosis >one-third of the total circumference and calcification present in the total circumference. FC was selected otherwise. Asymptomatic brain injury was assessed by diffusion-weighted magnetic resonance imaging. RESULTS: AC and FC were selected in 95 (35%) and 175 patients, respectively. AC patients were 10 years older ( P  < 0.001) and had higher EuroSCORE II (2.7 ± 3.4 vs 1.7 ± 1.9, P  =   0.002). The median cardiopulmonary time and cross-clamp times were not significantly different. No patients died in hospital. There was no immediate stroke in either group during 48 h after surgery. Asymptomatic brain injury was detected in 25 (26%) and 27 (15%) AC and FC patients, respectively, P  = 0.03. CONCLUSIONS: We believe our CT-based perfusion strategy using AC or FC minimized brain embolic rates. AC can be a good alternative to prevent brain embolization for minimally invasive cardiac surgery patients with advanced atherosclerotic disease.